2016
DOI: 10.1021/acschemneuro.5b00342
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Modulation as Effective Treatment for Dravet Syndrome in a Zebrafish Mutant Model

Abstract: Dravet syndrome (DS) is a severe epilepsy syndrome that starts within the first year of life. In a clinical study, add-on treatment with fenfluramine, a potent 5-hydroxytryptamine (5-HT) releaser activating multiple 5-HT receptor subtypes, made 70% of DS children seizure free. Others and we recently confirmed the efficacy of fenfluramine as an antiepileptiform compound in zebrafish models of DS. By using a large set of subtype selective agonists, in this study we examined which 5-HT receptor subtypes can be ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(134 citation statements)
references
References 67 publications
9
122
0
3
Order By: Relevance
“…A subsequent study found that clemizole has activity at 5-HT 2A and 5-HT 2B receptors in a radioligand binding assay, suggesting that a serotonergic mechanism may be responsible for its anti-epileptic activity (Griffin et al, 2017). Interestingly, fenfluramine, an inducer of serotonin (5-hydroxytrypamine, 5-HT) release, which was found to have some efficacy in improving seizures in individuals with Dravet syndrome (Ceulemans et al, 2012), also reduced seizure activity in zebrafish scn1lab mutants and morphants, suggesting conservation of pharmacological pathways (Dinday and Baraban, 2015; Zhang et al, 2015; Sourbron et al, 2016). …”
Section: Zebrafish Models Of Neurodevelopmental Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study found that clemizole has activity at 5-HT 2A and 5-HT 2B receptors in a radioligand binding assay, suggesting that a serotonergic mechanism may be responsible for its anti-epileptic activity (Griffin et al, 2017). Interestingly, fenfluramine, an inducer of serotonin (5-hydroxytrypamine, 5-HT) release, which was found to have some efficacy in improving seizures in individuals with Dravet syndrome (Ceulemans et al, 2012), also reduced seizure activity in zebrafish scn1lab mutants and morphants, suggesting conservation of pharmacological pathways (Dinday and Baraban, 2015; Zhang et al, 2015; Sourbron et al, 2016). …”
Section: Zebrafish Models Of Neurodevelopmental Disordersmentioning
confidence: 99%
“…Based on the serotonergic mechanism of fenfluramine, (Sourbron et al, 2016) tested selective 5-HT receptor agonists in scn1lab mutants and found that 5-HT 1D , 5-HT 2C , and 5-HT 2A agonists reverse electrographic seizure activity. Also, Griffin et al (2017) screened a library of 5-HT-modulating compounds and found that lorcaserin and trazodone rescued seizure activity.…”
Section: Zebrafish Models Of Neurodevelopmental Disordersmentioning
confidence: 99%
“…Sourbron et al (2016) were able to demonstrate that selective 5-HT 1D -, 5-HT 1E -, 5-HT 2A -, 5-HT 2C -, and 5-HT 7 -R agonists significantly decreased epileptiform activity in a homozygous sodium voltage gated channel alpha subunit 1 (SCN1A) mutant zebrafish model for Dravet syndrome (Sourbron et al, 2016). …”
Section: Monoamines In Epilepsy: Preclinical and Clinical Evidencementioning
confidence: 99%
“…Indeed, it has been shown that a genetic manipulation of zebrafish can result in reduced 5-HT content and increased seizure activity (Sourbron et al, 2016). However, Giorgi et al (2005) have reported that dosage regimens of MDMA that do not result in 5-HT depletion still result in increased seizure susceptibility.…”
Section: Discussionmentioning
confidence: 99%